2015
DOI: 10.1159/000437356
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Aralia elata</i></b> Prevents Neuronal Death by Downregulating Tonicity Response Element Binding Protein in Diabetic Retinopathy

Abstract: Background/Aims: The present study addresses the role of tonicity response element binding protein (TonEBP) in retinal ganglion cell (RGC) death in diabetic retinopathy and the impact of Aralia elata extract on the TonEBP/RGC interaction. Methods: Diabetes was induced in C57BL/6 mice by intraperitoneal injection of streptozotocin (STZ). Control mice received phosphate-buffered saline. After five injections of STZ or saline buffer, A. elata extract was administered by daily oral tube feeding for 7 weeks. All mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Kim et al (2015c) during a study on diabetic mice indicated that A. elata could modulate diabetic retinal neurodegeneration by prevention of RGC apoptosis and by decrease of TonEBP , AR and NF‐κB expression. Therefore, this herb is a promising agent for treatment of diabetes retinopathy due to its inhibition activity on neuronal toxicity and inflammation, leading to neuronal death (Kim et al, 2015c).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2015c) during a study on diabetic mice indicated that A. elata could modulate diabetic retinal neurodegeneration by prevention of RGC apoptosis and by decrease of TonEBP , AR and NF‐κB expression. Therefore, this herb is a promising agent for treatment of diabetes retinopathy due to its inhibition activity on neuronal toxicity and inflammation, leading to neuronal death (Kim et al, 2015c).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, targeting the regulatory network of NFAT5 may be an alternative approach to treat diabetic nephropathy. In this regard, the extract from plant Aralia elata has been recently shown to prevent neuronal death by downregulating NFAT5 and AR in mice with diabetic retinopathy, although which regulatory pathway it affects remains unknown [46] .…”
Section: Agc Protein Kinasesmentioning
confidence: 99%
“…In previous reports, Chaenomeles sinensis fruit was demonstrated to show neuroprotective effects against Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)-induced neurotoxicity in in vivo and in vitro [25]. Glycyrrhizae radix prevented Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)-induced neurotoxicity in cultured neurons [26]. Glycyrrhizae radix have been proved for its memory-enhancing effect and its anticholinesterase activity [23,27].…”
Section: Introductionmentioning
confidence: 98%
“…Glycyrrhizae radix have been proved for its memory-enhancing effect and its anticholinesterase activity [23,27]. Studies have reported neuronal protective effects of Aralia elata in some animal models [13,28]. Therefore, it was hypothesized that mixture of these three plants, possessing anti-oxidant and anti-inflammatory activities, might show more effective and synergistic neuroprotective effect with the reduction of possible individual toxicity due to large quantity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation